Shakespeare's Contemporary Resonance in Iran: Historical Context and Contemporary Representation - Mohsen Hanif; Mahbubeh Rostami (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This article examines the reception and interpretation of Shakespeare’s works in modern-day Iran, beginning with an overview of the Qajar Dynasty (1789–1925) and focusing on Post-Revolutionary Iran. The study aims to illuminate an often-overlooked aspect: a significant shift in attitudes toward Shakespeare’s plays between pre- and post-Revolutionary Iran, shaped by the dominant policies and ideologies of each era. Prior to the 1979 Iranian Revolution, adaptations of Shakespearean works such as Macbeth and Hamlet demonstrated discernible political orientations. In contrast, post-Revolution adaptations, including Tardid and Mortal Wound, adopted a more sophisticated moralistic perspective. This transformation extended not only to thematic content but also to the medium of adaptation. During the pre-Revolution period, Shakespeare’s plays were primarily translated into dramatic performances. However, the post-Revolutionary era saw a shift toward visual adaptations, including cinematic productions and home-video renditions. The contrast between these periods offers insights into Iran’s contemporary outlook, revealing the interplay between historical power structures and the reception of Shakespeare’s works. This study highlights the extent to which prevailing systems of authority shape the acceptance and adaptation of cultural expressions across distinct historical contexts.